1989
DOI: 10.1093/brain/112.4.1011
|View full text |Cite
|
Sign up to set email alerts
|

Different Interhemispheric Transfer of Kanji and Kana Writing Evidenced by a Case With Left Unilateral Agraphia Without Apraxia

Abstract: Recent neuropsychological studies have revealed that the processing of kanji (the Japanese morphograms) and kana (the Japanese syllabograms) involves different intrahemispheric mechanisms. We describe a patient showing left unilateral agraphia without apraxia for kanji, but not for kana, who was diagnosed by magnetic resonance imaging as having a lesion of the posterior body of the corpus callosum. This patient indicates that different neural pathways are used for kanji and kana not only intrahemispherically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…None of the cases exhibited aphasia, and their ability to read aloud under conditions of free vision was excellent. Callosal signs other than somesthetic ones have been reported previously for cases 1 [4]and 2 [5, 6, 7]. …”
Section: Methods and Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…None of the cases exhibited aphasia, and their ability to read aloud under conditions of free vision was excellent. Callosal signs other than somesthetic ones have been reported previously for cases 1 [4]and 2 [5, 6, 7]. …”
Section: Methods and Resultsmentioning
confidence: 73%
“…The autopsy in case 1 revealed lesions localized to the posterior truncus of the corpus callosum (for MRI of case 1, see Kawamura et al [4]). MRI in case 2 revealed lesions throughout the corpus callosum except in the rostrum [5, 6], and in case 3 it revealed lesions in the caudoventral part of the posterior truncus (fig.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Several clinical studies have also alluded to this hypothesis. Global and permanent alexia and apraxia, as well as other disorders of language, have been shown to relate to the interference of flow from the left hemisphere to the right across the posterior corpus callosum [6,7]. Egaas et al [34] examined 51 autistic patients (age 3-42 years) and found that the overall size reduction in the corpus callosum was concentrated in the posterior subregions where parietal lobe fibres are known to project [13].…”
Section: Discussionmentioning
confidence: 99%
“…6, *2). The somatosensory information from the left hand necessary for kinesthetic reading is thought to be transferred to the left superior parietal lobule via the anterior or dorsal part of the posterior truncus of the corpus callosum [13], although kana and kanji may not be transferred via exactly the same portion of the corpus callosum [29]. …”
Section: Discussionmentioning
confidence: 99%